2012
DOI: 10.1890/es11-000375.1
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the intrinsic parameters of propagule pressure: implications for bio‐invasion

Abstract: Abstract. Much effort has been devoted to understanding the factors promoting species colonisation, and processes that may cause small incipient populations to fail. Post colonisation and community level processes are proving to be less reliable predictors of initial population size and propagule pressure is now posited as a key predictor of species establishment. Yet, empirical studies manipulating the intrinsic parameters of propagule pressure, such as arrival frequency (number), and intensity (size) are lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 54 publications
(56 reference statements)
2
16
0
Order By: Relevance
“…These limitations of inference from historical data demonstrate that experimental studies are important to improve our understanding of how the temporal distribution of introduced individuals affects invasion success. Apart from the experimental Daphnia introductions by Drake et al (2005), we know of only one other such study: Hedge et al (2012) performed colonization experiments with larvae of the pacific oyster Crassostrea gigas and found higher population growth with frequent small introduction events compared to fewer large introduction events, a phenomenon that they attributed to reduced intraspecific competition or increased facilitation if individuals arrive at different time points.…”
Section: Discussionmentioning
confidence: 99%
“…These limitations of inference from historical data demonstrate that experimental studies are important to improve our understanding of how the temporal distribution of introduced individuals affects invasion success. Apart from the experimental Daphnia introductions by Drake et al (2005), we know of only one other such study: Hedge et al (2012) performed colonization experiments with larvae of the pacific oyster Crassostrea gigas and found higher population growth with frequent small introduction events compared to fewer large introduction events, a phenomenon that they attributed to reduced intraspecific competition or increased facilitation if individuals arrive at different time points.…”
Section: Discussionmentioning
confidence: 99%
“…Propagule pressure relates the numerical size (or the abundance of arriving individual organisms) and arrival rates of propagules, which are in turn comprised of individual organisms (Lockwood, Cassey & Blackburn , ). We would argue that this term also encompasses the diversity and quality of arriving propagules (Hedge, O'Connor & Johnston ). Numerous studies have now demonstrated the strong effects of individual quality on settlement probability and postsettlement fitness (Pechenik, Wendt & Jarrett ), and effects resulting from the diversity of arriving propagules should not be ignored (Lockwood, Cassey & Blackburn ).…”
Section: Introductionmentioning
confidence: 99%
“…Where empirical studies have been conducted, however, the relationship between propagule pressure and colonization is usually expressed as a simple dose‐response function relating propagule size with the subsequent number of individuals surviving until census (Ruiz et al . ; Clark & Johnston , ; but see Hedge, O'Connor & Johnston ). Further, despite the intensity of study that interspecific diversity has engendered over the past few decades (Loreau et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While density‐dependent decreases in individual performance are common in invasive species (Burgess and Marshall , Hedge et al. ), it is the direction of the interaction that is surprising. Poorer‐quality individuals often experience negative‐density dependent effects more strongly than higher‐quality individuals (Rubenstein , Clutton‐Brock et al.…”
Section: Discussionmentioning
confidence: 99%